"Part of the Conversation": A Qualitative Study of Oncology Healthcare Professionals' Experiences of Integrating Standardized Assessment and Documentation of Complementary Medicine. (February 2022) - Balneaves, Lynda G.; Watling, Cody Z.
Introduction: The use of complementary medicine (CM) among individuals with cancer is common, however, it is infrequently assessed or documented by oncology healthcare professionals (HCPs). A study implementing standardized assessment and documentation of CM was conducted at a provincial cancer agency. The purpose of this study was to understand the perspectives and experience of oncology HCPs who took part in the study, as well as withdrew, regarding the feasibility and the challenges associated with assessment and documentation of CM use. Methods: An interpretive descriptive study methodology was used. A total of 20 HCPs who participated, managed staff, or withdrew from the study were interviewed. Interviews were recorded and transcribed verbatim. Thematic, inductive analysis was used to code and analyse themes from the data. Results: Oncology HCPs who participated in the study felt that CM use was common among patients and recognized it went underreported and was poorly documented. Facilitating factors for the implementation of standardized assessment and documentation of CM use included having a standard assessment form, embedding assessment within existing screening processes, and leveraging self-report by patients. Barriers included limited time, perceived lack of knowledge regarding CM, hesitancy to engage patients in discussion about CM, and lack of institutional support and resources. Recommendations for future implementation included having explicit policies related to addressing CM at point-of-care, leveraging existing electronic patient reporting systems, including the electronic health record, and developing information resources and training for HCPs. Conclusions: With the high prevalence of CM use among individuals with cancer, oncology HCPs perceive addressing CM use to be feasible and an essential part of high-quality, person-centered cancer care. Institutional and professional challenges, however, must be overcome to support the assessment, documentation and discussion of CM in patient-HCP consultations.